Synergistic interplay between arbuscular mycorrhizal fungi and fern manure compost tea suppresses common tomato phytopathogens and pest attacks on-farm - Mbogning, Sylviane; Okiobe, Simon Thierry; Theuerl, Susanne; Nwaga, Dieudonne (Frontiers in Horticulture, 2024)
Actually, there are intensive efforts towards eco-friendly integrated agricultural management measures to control plant diseases and pests. One of the most promising approaches is the use of arbuscular mycorrhizal fungi (AMF) in combination with organic biopesticides such as eagle fern manure (FM) compost tea. However, their effects have been mainly studied independently from each other. The potential interactions between belowground plant-associated microorganisms such as AMF and aboveground foliar application of biopesticide to mitigate common tomato phytopathogens and pests remain untapped, particularly under on-farm conditions. In a randomized complete block design, the impact of inoculating tomato seedlings with a selected AMF consortium and beyond that, the impact of mycorrhized plants receiving three different doses of FM compost tea (0 %, 5 %, and 10 %) on the control of tomato-specific plant diseases and pests, and subsequently on the crop yield were examined. The present study demonstrated a seven-fold increase in the rate of mycorrhizal root colonization (from 10 to 70 %) in tomato plants that received the combined application of AMF and 10 % FM compost tea compared to the control plants that did not receive AMF inoculum and FM compost tea. The combination of AMF and FM compost tea application led to positive synergistic effects that promoted beneficial effects in suppressing the incidence and severity of common tomato diseases and pests. The magnitude of these synergistic effects increased with AMF inoculation and FM compost tea dosage, culminating in greater suppression of tomato plant diseases and pests and, moreover, in an increase in fruit yield compared to control plants. The combination of AMF and 10 % FM compost tea revealed a higher suppressive ability against most pathogens and insect attacks. This was evidenced by a 71.3 % and 94.7 % total reduction in the incidence and severity, respectively, compared to control plants. This is the first time that pre-inoculation of AM, combined with FM compost tea application has been reported, as a potential biocontrol alternative to suppress common tomato pathogens and pests while increasing cherry tomato yields sustainably.